Program Aksi Kolaborasi Kampus Mengajar Angkatan 6 di SMP Negeri 4 Liang - Hardianti; Tangkal, Sisilia Febrianti; Izzati, Wa Ode Irniyanti; Basyae, Rifka Anisa Cikal Bakal Rambu (Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The Kampus Mengajar Program Batch 6 is an initiative aimed at improving the quality of education in remote areas through student involvement in teaching and school development activities. This article discusses the mentoring experience in the Collaborative Action Program of Kampus Mengajar at SMP Negeri 4 Liang, Banggai Kepulauan Regency, Central Sulawesi. The mentoring includes the role of field supervisor in facilitating students in teaching activities, evaluations, and program development at the school. The implementation methods include coordination, guidance, and evaluation to ensure the program's effectiveness. The results of the mentoring indicate an improvement in students' teaching skills and a positive impact on the students. Through the methods of coordination, guidance, evaluation, and program implementation, this article demonstrates how the Merdeka Belajar Kampus Merdeka (MBKM) encourages collaboration and innovation in education, providing benefits to students, partner schools, and field supervisors.